Formula dan Tema Syair Pengiring Tari Aceh Likok Pulo - Anwar, Humaira (Universitas Hamzanwadi, 2020)
Likok Pulo Dance is one of the traditional dances from Aceh that is accompanied by song which called syair. Syair sung by the syeh throughout the dance. This dance originated from the Aceh Island (Pulau Aceh), Aceh Besar, Aceh, and was used as a way of preaching. As an oral literature, syair of the Likok Pulo Dance has formulas and themes. This study aims to describe the formula and theme. Descriptions of formulas and themes will be carried out with Albert Lord's formula and theme’s theory. This research method is a qualitative method with from the documents instrument. The results showed that the accompaniment of the Likok Pulo Dance contained the formula hai adôe, Allah, ya Allah, and the lon idang phrases. The theme for the accompaniment syair of the Likok Pulo Dance is zikir which is remember the God from the stories. This relates to the main purpose of the Likok Pulo Dance as one of the means of preaching in the past.